Advances in MEMS and Microfluidics‐Based Energy Harvesting Technologies. Issue 7 (9th February 2022) - Mahmud, M. A. Parvez; Bazaz, Sajad Razavi; Dabiri, Soroush; Mehrizi, Ali Abouei; Asadnia, Mohsen; Warkiani, Majid Ebrahimi; Wang, Zhong Lin
Abstract: Energy harvesting from mechanical vibrations, thermal gradients, electromagnetic radiations, and solar radiations has experienced rapid progress in recent times not only to develop an alternative power source that can replace conventional batteries to energize portable and personal electronics smartly but also to achieve sustainable self‐sufficient micro/nanosystems. Utilizing micro‐electromechanical system (MEMS) and microfluidics technologies through selective designs and fabrications effectively, those energy harvesters can be considerably downsized while ensuring a stable, portable, and consistent power supply. Although ambient energy sources such as solar radiation are harvested for decades, recent developments have enabled ambient vibrations, electromagnetic radiation, and heat to be harvested wirelessly, independently, and sustainably. Developments in the field of microfluidics have also led to the design and fabrication of novel energy harvesting devices. This paper reviews the recent advancements in energy harvesting technologies such as piezoelectric, electromagnetic, electrostatic, thermoelectric, radio frequency, and solar to drive self‐powered portable electronics. Moreover, the potential application of MEMS and microfluidics as well as MEMS‐based structures and fabrication techniques for energy harvesting are summarized and presented. Finally, a few crucial challenges affecting the performance of energy harvesters are addressed. Abstract : This review covers energy harvesting technologies such as piezoelectric, electromagnetic, electrostatic, thermoelectric, radio frequency, and solar to drive self‐powered portable electronics, reviewing their recent analytical performances and highlighting critical shortcomings yet to be resolved. In‐depth insights into future development of micro‐electromechanical system and microfluidics technologies are provided for a paradigm shift in the field of energy harvesting in the next decade.